Proceedings of KMI International Symposium 2013 on “Quest for the Origin of Particles and the Universe — PoS(KMI2013) 2015
DOI: 10.22323/1.208.0045
|View full text |Cite
|
Sign up to set email alerts
|

Constraining isocurvature perturbations with the 21cm emission from minihaloes

Abstract: We investigate the effects of isocurvature perturbations on the 21cm radiation from minihaloes (MHs) at high redshifts and examine constraints on the isocurvature amplitude and power spectrum using the next generation of radio telescopes such as the Square Kilometre Array. We find that there is a realistic prospect of observing the isocurvature imprints in the 21cm emission from MHs, but only if the isocurvature spectral index is close to 3 (i.e. the spectrum is blue). When the isocurvature fraction increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…For example, setting Φ+ (η i ) M p at initial times, the constraint on k is where N e is the number of e-folds between t i and the end of inflation, T rh is the reheating temperature, g * S (t 0 ) is the effective number of entropy degrees of freedom today. 7…”
Section: Fitting Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, setting Φ+ (η i ) M p at initial times, the constraint on k is where N e is the number of e-folds between t i and the end of inflation, T rh is the reheating temperature, g * S (t 0 ) is the effective number of entropy degrees of freedom today. 7…”
Section: Fitting Functionmentioning
confidence: 99%
“…If these fields are sufficiently secluded from both the inflaton sector and the SM sector (i.e. they are only very weakly interacting), the blue spectrum will survive long enough for them to be observable today [6] in the form of isocurvature perturbations [7][8][9][10]. 1 However, if the masses of order H do not undergo a transition to a different value at some point during inflation, the energy density dilution during inflation can make these noninflaton fields' isocurvature perturbations nearly impossible to observe directly even if they had a large amplitude blue isocurvature spectrum [15].…”
Section: Introductionmentioning
confidence: 99%
“…In [73], it was shown that spectral indices as large as n I = 3.8 (but not n I = 4) can be achieved in the context of a dynamical VEV breaking the Peccei-Quinn (PQ) symmetry. This is of interest because n I = 3 is considered to be observable for example by the Square Kilometer Array [72].…”
Section: Models: What Happens With a Dynamical Mass?mentioning
confidence: 99%
“…1 Scale-invariant isocurvature perturbations with negligible correlations with curvature perturbations are well constrained to be less than 3% of the adiabatic power [12,15,19,[65][66][67][68][69][70]. However, isocurvature spectra with very blue spectral indices can be unobservably small on long wavelengths, for which the measurements are strongly constraining, but have large amplitudes on short wavelengths, where the measurements are less constraining [71][72][73]. The case of a blue spectrum is qualitatively different from a "bump" in the spectrum because bumps usually involve a red part as well as a blue part, and because the blue spectrum here is envisioned to have a qualitatively extended k-space range over which an approximately constant blue spectral index persists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation